2017
DOI: 10.1097/jcn.0000000000000392
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Self-management Support for Improving Coronary Heart Disease and Self-management–Related Outcomes

Abstract: Introduction:Coronary heart disease (CHD) is associated with significant morbidity and mortality, including mental health comorbidity, which is associated with poor outcomes. Self-management is key, but there is limited access to self-management support. Internet-delivered interventions may increase access.Objective:The aim of this study was to conduct a systematic review to (1) determine the effectiveness of Internet-delivered CHD self-management support for improving CHD, mood, and self-management related ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…100 A systematic review on internet-delivered interventions in patients with CAD has shown that personalised, concrete support for behaviour change may have favourable outcomes; however, a considerable heterogeneity between studies with respect to the design and quality hinder sound conclusions. 101 Adherence Cardiovascular fixed-dose combination pills, or polypills, may help address the widespread lack of access and adherence to proved medicines. Adherence benefits from switching to a polypill resulted in risk factor changes that were at least as good as usual care across a wide variety of treatment patterns, including equally potent or more potent regimens.…”
Section: Behaviourmentioning
confidence: 99%
“…100 A systematic review on internet-delivered interventions in patients with CAD has shown that personalised, concrete support for behaviour change may have favourable outcomes; however, a considerable heterogeneity between studies with respect to the design and quality hinder sound conclusions. 101 Adherence Cardiovascular fixed-dose combination pills, or polypills, may help address the widespread lack of access and adherence to proved medicines. Adherence benefits from switching to a polypill resulted in risk factor changes that were at least as good as usual care across a wide variety of treatment patterns, including equally potent or more potent regimens.…”
Section: Behaviourmentioning
confidence: 99%
“…Review studies on the effectiveness of Internet-based interventions have indicated that users are satisfied and that they result in improved behaviors and clinical outcomes compared with nonusers for patients with CAD [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the frequency and duration of the intervention could not be established, the authors concluded that telecommunication health education models can assist in secondary prevention of CAD and narrow the gap between evidence of the benefits of rehabilitation programs and the difficulty of implementation in clinical practice (20) . In another systematic review of internet interventions for promoting CAD self-management, the authors concluded there is a need for more robust and well-delineated clinical trials (21) . These studies should explore how interventions work and how to improve participants' adherence to rehabilitation programs (21) .…”
Section: Discussionmentioning
confidence: 99%
“…In another systematic review of internet interventions for promoting CAD self-management, the authors concluded there is a need for more robust and well-delineated clinical trials (21) . These studies should explore how interventions work and how to improve participants' adherence to rehabilitation programs (21) . In 2016, the International Council of Cardiovascular Prevention and Rehabilitation (ICCPR) released strategies for implementing cardiac rehabilitation programs in developing countries (22) .…”
Section: Discussionmentioning
confidence: 99%